HOTS-Based Qiro'ah Textbook Development to Enhance Arabic Learners' Extensive Reading Skills - Nashoih, Afif Kholisun (Islamic Faculty of KH. A. Wahab Hasbullah University, Jombang, Indonesia, 2024)
This research is motivated by the weak skills in reading contemporary Arabic texts among students, caused by the lack of references for Arabic language learners regarding modern Arabic. Therefore, this study aims to develop a textbook for contemporary Arabic language, designed with Higher Order Thinking Skills (HOTS) approach, with the goal of enhancing the extensive reading skills of learners. The method used in this research is Research and Development (R&D) adopting Prof. Sugiyono's development model. Data collection in this research is carried out using observation, questionnaires, and tests. This research resulted in a textbook for contemporary Arabic language comprising 14 chapters. Each chapter consists of reading texts, a list of difficult vocabulary, text content summaries, and 5 types of exercises organized based on HOTS theory. The developed textbook is categorized as highly appropriate based on expert validation results with a score of 91% from the first validator and 88% from the second validator. Meanwhile, the field trial results state that this textbook is capable of improving student learning outcomes, as indicated by the pre-test score of 60.89% and the post-test score of 87.32%. Thus, there is a difference of 26.43% indicating a significant improvement. Therefore, the textbook is able to enhance the reading skills of Arabic texts for advanced levels, with a high level of text difficulty as well